Correlation of Maternal Comorbidities and Neonatal Outcomes in Patients With Non-Reassuring Fetal Status Undergoing Caesarean Section - Nasrudin, Nasrudin; Priyanto, Edy; Suardi, Dodi (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: Non-reassuring fetal status (NRFS) is an obstetric emergency characterized by abnormal fetal heart rate patterns requiring immediate intervention, often through cesarean section. Maternal comorbidities such as obesity, hypertension, and anemia are suspected to increase the risk of NRFS and adversely affect neonatal outcomes, particularly in developing countries. This study aimed to evaluate the relationship between maternal comorbidities and neonatal outcomes, including low birth weight (LBW), APGAR scores, and the need for Neonatal Intensive Care Unit (NICU) admission, in NRFS cases undergoing cesarean section at Prof. Dr. Margono Soekarjo Hospital, Purwokerto, from September 2023 to April 2024.Methods: A cross-sectional study used secondary (medical) data with total sampling. Bivariate and multivariate logistic regression analyses reported odds ratios (ORs) and 95% confidence intervals (CIs). A p-value of <0.05 was considered statistically significant.Result: Maternal obesity, hypertension, and anemia were significantly associated with LBW, low APGAR scores, and NICU admission. All comorbidities showed ORs <1, indicating increased risk for adverse neonatal outcomes.Conclusion: There was a significant correlation between maternal comorbidities and poor neonatal outcomes in NRFS cases delivered via cesarean section.Hubungan antara Komorbiditas Maternal dan Luaran Neonatus pada Pasien dengan Non-Reassuring Fetal Status yang Menjalani Seksio SesareaAbstrak Tujuan: Non-reassuring fetal status (NRFS) adalah kondisi kegawatdaruratan obstetri yang ditandai oleh pola detak jantung janin abnormal dan membutuhkan intervensi segera, sering berupa seksio sesarea. Komorbiditas maternal seperti obesitas, hipertensi, dan anemia diduga berperan dalam meningkatkan risiko NRFS dan memengaruhi luaran neonatal, terutama di negara berkembang. Penelitian ini bertujuan mengevaluasi hubungan antara komorbiditas maternal dan berat badan lahir rendah (BBLR), skor APGAR, dan kebutuhan perawatan Neonatal Intensive Care Unit (NICU) pada pasien NRFS yang menjalani seksio sesarea di RSUD Prof. Dr. Margono Sokearjo Purwokerto dari September 2023 hingga April 2024.Metode: Penelitian potong lintang ini menggunakan data (rekam medis) dengan teknik total sampling. Analisis bivariat dan multivariat dilakukan menggunakan regresi logistik dengan odds ratio (OR) dan interval kepercayaan 95%. Nilai p <0,05 dianggap signifikan.Hasil: Obesitas, hipertensi, dan anemia maternal secara signifikan berhubungan dengan BBLR, skor APGAR rendah, dan kebutuhan NICU. Semua komorbiditas menunjukkan odd ratio <1, mengindikasikan peningkatan risiko terhadap luaran neonatal yang merugikan.Kesimpulan: Terdapat hubungan signifikan antara komorbiditas maternal dan luaran neonatal yang buruk pada pasien NRFS yang menjalani seksio sesarea.